A history of religion in 5 1/2 objects : bringing the spiritual to its senses - Plate, S. Brent, 1966- (Beacon Press, 2014)
"A leading scholar brings religion to its senses by exploring the importance of physical objects and sensory experience in the practice of religion Humans are needy. We need things: objects, keepsakes, knickknacks, bits and pieces, junk and treasure. As Brent Plate argues in A History of Religion in 5 1/2 Objects, exploring the stuff of everyday existence is a fresh window into the way humans have formed religious communities, performed rituals, and connected with the realm of the sacred. Beginning with the human desire to connect (evoked by "1/2"), Plate tells the stories of five types of ordinary objects that people have engaged with in sensory, symbolic, and sacred ways: stones, crosses, incense, drums, and bread. These material objects, each of which strongly engages one of our five senses, have been used in religious ceremonies throughout human history and across the world. A History of Religion in 5 1/2 Objects shows us that basic, material connections stand at the heart of religious traditions, as humans quest for meaningful, fulfilling lives. As Plate looks at each of these objects, he traces the history of the world's religions and finds remarkable similarities and recurring themes throughout the millenia. We learn why incense is used by Hindus at a celebration of the goddess Durga in Banaras, by Muslims at a wedding ceremony in West Africa, and by Roman Catholics at a mass in upstate New York. And why stones, in the form of cairns, grave markers, and monuments, became connected with places of memory across the world. A History of Religion in 5 1/2 Objects moves our understanding of religion away from the current obsessions with God, fundamentalism, and science. Religion, Plate shows, has more to do with our bodies than with our beliefs"--